The Influence of Social Media Marketing and Product Variations on Buying Interest in Courses at Easy Course Institutions in Makassar City - Pamungkas, Mahesa Angel; Romadhoni, Buyung; Aulia, Aulia (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the effect of social media marketing and product variation on the interest in purchasing courses at Easy Course Institute in Makassar City. The research uses a quantitative approach, with data collected through questionnaires distributed to 130 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 30. The results indicate that social media marketing and product variation have a positive and significant effect on course Purchase Intention. These findings suggest that the more effective the social media marketing strategies and the more varied the courses offered, the higher the interest of potential participants. Therefore, Easy Course Institute should optimize social media utilization and enhance course variations to attract more participants.